An iOS image processor for fringe pattern analysis - Teo, Josias Yi Si (2014)
Many fields in science and engineering use fringe patterns for various purposes. One particular application is in the fringe projection system (FPS) for surface profilometry. A reference FPS consisted of a LCD projector, a laptop and a standalone camera to scan objects against a black, non- reflective screen. It was limited to an enclosed room because readings would be affected by excess ambient light. Thus, this project aimed to overcome these restrictions, in hopes of creating a fully mobile FPS. An iOS application was developed for an iPad, incorporating necessary algorithms to achieve a similar 3D model. The iPad was benchmarked against the reference Macbook Air, and was more cost-effective, even though it took longer to complete the task. This was a good indication to realizing a completely mobile FPS. Future works could delve into creating a structured light emitter- sensor mountable on a mobile device.